2017
DOI: 10.1002/elsc.201600213
|View full text |Cite
|
Sign up to set email alerts
|

Removal of dimethylphenols and ammonium in laboratory‐scale horizontal subsurface flow constructed wetlands

Abstract: Phenolic compounds in industrial wastewaters are toxic pollutants and pose a threat to public health and ecosystems. More recently, focus is being directed toward combining the treatment of these compounds with a cost‐effective and environmentally sound technology. The removal efficiency of dimethylphenol and ammonium nitrogen was studied, for the first time, in three different laboratory‐scale horizontal subsurface flow constructed wetlands planted with Juncus effusus. Two of the wetlands used were filled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…The high levels of these compounds applied in the CW probably created a toxic environment that affected the development of the microbial community, especially in the planted systems where an enhanced aerobic environment is usually established. High toxicity can be caused not only by increased phenols concentration, but also due to increased generation of intermediates during phenols transformation, as elsewhere reported [25].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The high levels of these compounds applied in the CW probably created a toxic environment that affected the development of the microbial community, especially in the planted systems where an enhanced aerobic environment is usually established. High toxicity can be caused not only by increased phenols concentration, but also due to increased generation of intermediates during phenols transformation, as elsewhere reported [25].…”
Section: Discussionsupporting
confidence: 66%
“…This study revealed higher removal efficiencies by 10-15% in the unplanted than the planted CW for organic matter and specific phenolic compounds. Though the role of plants in CW still remains a topic of discussion, it is generally believed, and several studies have shown, that the presence of plants contributes to the system's efficiency, with regards to organic matter and phenolic compounds [5,14,16,[25][26][27]. It is reported that the rhizosphere of the plants contributes to the creation of an aerobic microenvironment (i.e., P. australis transfers 5-12 g O 2 /m 2 /day through its roots) that stimulates the microorganism growth and, thus, the biodegradation of the organic matter and specific compounds contained in the influents [5,14,[28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is worth mentioning that a longer hydraulic retention time and larger contact area (surface) between wastewater and the bed media may increase the pH value 37 . In the same sense, the reason behind the increase of pH at the CW microcosms outlet may be related somehow to the enhanced aerobic conditions that dominate in the upper zone of cultivated CWs 20,28,38,39 . However, the results pointed out a relatively slight increase in the average pH of the treated effluent in CW6 compared to the other effluents.…”
Section: Resultsmentioning
confidence: 93%
“…Other removal pathways are also mediated by the secretion of root exudates [21,28,69], while plant uptake, precipitation or the dissolution, and the adsorption onto substrate grains would also contribute to further pollutants reduction in planted beds [2,6,17,21]. Several studies in the literature also report the improved performance of planted VFCWs over unplanted beds, indicating the positive role of plants presence in the VFCW system [2,[5][6][7]26].…”
Section: Vfcws Performancementioning
confidence: 99%
“…Biological processes mediated by the various microorganisms are believed to play a key role in pollutants removal in CWs [2,19]. In particular, microbial processes are considered the main pollutant removal mechanism of organic matter and nitrogen [16,[23][24][25][26]. Microorganisms develop naturally in the bed matrix, and mainly depend on the hydraulic conditions, wastewater characteristics, substrate characteristics, nutrient quality and availability, plants, and environmental factors, such as oxygen level, pH and temperature [22,27].…”
Section: Introductionmentioning
confidence: 99%